Posebnosti Istre kao prigranične regije Hrvatske - Sić, Miroslav (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2001)
This paper deals the particularities of Istria in the regional structure of Croatia. The significance of its geografhical position, level of economic development, then of its historical development and heritage. The regional identity of Istria is being analysed through three components: economic, political and cultural. The final part of the paper represents the trans-border functions of Istria and tendencies of the interregional cooperation in the area of Sjeverni Jadran (Northern Littoral).
Keywords: Croatia; državne meje; Hrvaška; Istra; Istria; obmejna območja; obmejno sodelovanje; regionalni razvoj; Slovenia; Slovenija